Association between horizontal violence and turnover intention in nurses: A systematic review and meta-analysis - Zhang, Yue; Yin, Rulan; Lu, Jing; Cai, Jianzheng; Wang, Haifang; Shi, Xiaoqing; Mao, Lifen (Frontiers in Public Health, 2022)
Background Horizontal violence is common in nurses. Most published studies have focused on horizontal violence and higher turnover rates in nurses; however, it lacks systematic reviews and meta-analyses. The purpose of this review is to quantitatively assess the correlation between horizontal violence and turnover intention in nurses. Methods Systematic review and meta-analysis were performed in accordance with PRISMA guidelines. The relationship between horizontal violence and turnover intention in nurses was obtained by systematically searching related literature in four English databases (Cochrane, PubMed, Embase, and CINAHL) and three Chinese databases (SinoMed, CNKI, and Wanfang) (up to 6 March 2022). The relationship between horizontal violence and turnover intention was evaluated using Fisher's z-value, which was then converted to r. STATA 16.0 was used to perform statistical analysis. The random-effects model was performed to synthesize data. Results A total of 14 studies with 6,472 nurses were included. A low-positive correlation of horizontal violence with turnover intention was found (pooled r=0.32 [0.29–0.34]). Subgroup analysis showed that sample size and quality were not the source of heterogeneity. Measurement tool was the source of heterogeneity. Although geographic region might not be the source of heterogeneity, further subgroup analysis of the country reveals heterogeneity. The funnel plot and Egger's test showed no publication bias. Conclusion Horizontal violence had a low positive correlation with turnover intention in nurses. Nurses who experienced horizontal violence were more likely to leave or change careers than those who did not experience horizontal violence. This finding helps to draw attention to horizontal violence by nursing managers and implement effective interventions for nurses, so as to reduce nurses' turnover.